Identifying Opportunities for Developing Nature-Based Sport Tourism to Improve Health in Papua: A Bibliometric Analysis of Research Over Ten Years - Tri Setyo Guntoro; Yudik Prasetyo; Miftah Fariz Prima Putra; Dewi Nurhidayah; Evi Sinaga; Ela Yuliana; Fitri Agung Nanda (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to examine research trends around nature-based tourism, event-based sports tourism, and their relationship with government policies to identify potential opportunities for sustainable sports tourism development in Papua.